Nanohollow Carbon for Rechargeable Batteries: Ongoing Progresses and Challenges - Jiang, Jiangmin; Nie, Guangdi; Nie, Ping; Li, Zhiwei; Pan, Zhenghui; Kou, Zongkui; Dou, Hui; Zhang, Xiaogang; Wang, John (Nano-Micro Letters, 2020)
Among the various morphologies of carbon-based materials, hollow carbon nanostructures are of particular interest for energy storage. They have been widely investigated as electrode materials in different types of rechargeable batteries, owing to their high surface areas in association with the high surface-to-volume ratios, controllable pores and pore size distribution, high electrical conductivity, and excellent chemical and mechanical stability, which are beneficial for providing active sites, accelerating electrons/ions transfer, interacting with electrolytes, and giving rise to high specific capacity, rate capability, cycling ability, and overall electrochemical performance. In this overview, we look into the ongoing progresses that are being made with the nanohollow carbon materials, including nanospheres, nanopolyhedrons, and nanofibers, in relation to their applications in the main types of rechargeable batteries. The design and synthesis strategies for them and their electrochemical performance in rechargeable batteries, including lithium-ion batteries, sodium-ion batteries, potassium-ion batteries, and lithium–sulfur batteries are comprehensively reviewed and discussed, together with the challenges being faced and perspectives for them. Highlights 1 The synthesis strategies of nanohollow carbon materials, including nanospheres, nanopolyhedrons, and nanofibers are summarized. 2 Nanohollow carbon materials used as electrode materials in several types of rechargeable batteries are reviewed. 3 The challenges being faced and perspectives of nanohollow carbon materials are discussed.